Women Factor Analysis Workers Who Affect Fertility Rates in the Banjar Tribe in Banjarmasin City, 2010-2024 - Chairul Sa'roni; Deasy Arisanty (JPG (Jurnal Pendidikan Geografi), 2025)
This study aims to analyze in depth the influence of female workers on fertility rates among the Banjar ethnic community in Banjarmasin City between 2010 and 2024. This phenomenon is important because changes in women's roles in the workforce are not only related to economic aspects but also impact social and demographic dynamics, particularly birth rates. Using a quantitative approach, this study relies on secondary data sourced from the Central Statistics Agency (BPS) and the National Population and Family Planning Agency (BKKBN). Through regression analysis, it was found that the increasing number of women working as professionals actually contributes positively to population growth. This can be explained because women with economic stability tend to feel more financially capable of raising children. Conversely, increasing female representation in parliament has shown a tendency to reduce fertility rates. This condition indicates that women's involvement in the political sphere and public decision-making is related to preferences for delaying or limiting the number of children, which ultimately affects birth rates. The findings of this study emphasize that women's socioeconomic factors have a significant influence on population dynamics. Therefore, public policies in the field of employment and family development need to be designed by considering the balance between women's productive roles in the public sector and their reproductive decisions.